2004
DOI: 10.2214/ajr.183.1.1830183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Angioarchitecture of Pulmonary Sequestration in Pediatric Patients Using 3D MDCT Angiography

Abstract: MDCT angiography with 3D rendering shows the anomalous feeding artery and the draining veins that allow a diagnosis of pulmonary sequestration. These features may prove useful in distinguishing intra- and extralobar sequestration and in surgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…This study provides the best evaluation of the vascular anatomy of the lesion and the appearance of the lesion itself, and of the diaphragm and remainder of the lung. 10 Although magnetic resonance imaging can be performed without radiation and does provide excellent vascular visualization, it does not provide the same high-quality evaluation of the pulmonary parenchymal part of the lesion. 11 In addition to the concern for recurrent infections in ILS, there is also a currently recognized risk in cystic adenomatoid malformation or congenital lung cysts for development of pleuropulmonary blastoma.…”
Section: Denouement and Discussionmentioning
confidence: 99%
“…This study provides the best evaluation of the vascular anatomy of the lesion and the appearance of the lesion itself, and of the diaphragm and remainder of the lung. 10 Although magnetic resonance imaging can be performed without radiation and does provide excellent vascular visualization, it does not provide the same high-quality evaluation of the pulmonary parenchymal part of the lesion. 11 In addition to the concern for recurrent infections in ILS, there is also a currently recognized risk in cystic adenomatoid malformation or congenital lung cysts for development of pleuropulmonary blastoma.…”
Section: Denouement and Discussionmentioning
confidence: 99%
“…The usefulness of MDCT for visualization of the aberrant artery in pulmonary sequestration has been demonstrated in infants and school-age children [2,3,7]. In the present cases, MDCT was used to visualize ultra-fine aberrant arteries (as small as 3.0 mm in diameter) in neonates weighing as little as 2900 g without deep sedation.…”
Section: Discussionmentioning
confidence: 78%
“…Diagnosis of pulmonary sequestration where the aberrant artery has been detected by contrast computed tomography (CT) [1][2][3] or magnetic resonance angiography (MRA) [1,[4][5][6] instead of by conventional angiography is becoming more common. However, the aberrant artery is difficult to visualize in neonates because of the fineness of the artery and neighboring respiratory and cardiac motion.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that spiral CT demonstrates two thirds of the arterial supplies, and most venous drainages cannot be shown (8,9). Whereas, MDCT is capable to simultaneously demonstrate the arterial supply, venous drainage and parenchymal changes in a single examination (10,11). We were able to demonstrate arterial supply and venous drainage in all thesix patients who underwent MDCT.…”
mentioning
confidence: 70%
“…Arteriography is the method of choice to demonstrate the systemic vessels supplying the abnormal portion of the lung (4,5). Several studies mainly consisting of case reports have shown that magnetic resonance imaging (MRI), helical computed tomography (HCT) and multidetector computed tomography (MDCT) angiography may be used to demonstrate the aberrant vasculature and the bronchial anatomy (6)(7)(8)(9)(10)(11). In the study we aimed to evaluate the accuracy of MDCT in demonstrating the feeding artery and draining veins.…”
Section: Evaluation Of Diagnostic Accuracy Of Computed Tomography To mentioning
confidence: 99%